EVALUASI PROGRAM PEMBELAJARAN GURU MATA PELAJARAN EKONOMI SEKOLAH MENENGAH ATAS (SMA) NEGERI DAN SWASTA DI KABUPATEN TULUNGAGUNG - Hendro Dwi Baskoro; Hari Wahyono; Nasikh Nasikh (Jurnal Pendidikan Ekonomi, 2017)
The purpose of this research is (1) to know the quality of learning device ofeconomic teacher learning in Public High School and Private atTulungagung Regency; (2) to know the quality of the implementation ofeconomics teacher learning in Public High School and Private atTulungagung Regency; (3) to know the quality of evaluation of economicteacher learning in Public High School and Private at Tulungagung Regency.This research uses evaluation approach. Research data in the form ofexposure of resource persons from Senior High School 1 Kedungwaru andSenior High School PGRI Kalangbret in Tulungagung Regency. Datacollection is done by interview, observation and documentation. Analysis ofdata used is data collection and take conclusions. While checking thevalidity of data findings is done by extension of participation, trianggulasiand diligence of observation. DOI: https://dx.doi.org/10.17977/UM014v10i22017p118